Teachers' Perspectives on Using AI in Teaching English at High Schools in Jombang - Fanani, Achmad; Nurcahyani, Dwi; Najih, Aizun; Bakri, Bakri; Zaki, Muhamad (Contemporary Journal of Applied Sciences, 2024)
This study examines high school teachers' perspectives on using Artificial Intelligence (AI) in teaching English in Jombang, East Java. Employing a mixed-method approach, it involves surveys of 42 participants (2 teachers and 40 students) and interviews with 4 teachers and 4 students. The findings show that AI is seen as an effective tool for enhancing English learning, with most participants expressing positive attitudes. Younger teachers demonstrate higher readiness to adopt AI, though challenges like limited technology access and insufficient training persist. The study emphasizes AI's transformative potential in English education, highlighting the importance of professional development and addressing practical barriers to maximize its benefits in teaching methodologies and student engagement